Wideband vibration control in multi degree of freedom system: experimental verification using LabVIEW - Ladipo, Ismail; Abdul Muthalif, Asan Gani (Elsevier, 2012)
The attenuation of vibration in a multi degree of freedom system is presented in this paper. The objective is to employ the instrumentation capability of LabVIEW in the implementation of an Active Dynamic Vibration Absorber (ADVA). To reduce vibration, the ADVA and the multi degree of freedom systems used is taken to be an intelligent coupled system that determines the resonance frequency and subsequently tuned itself to reduce vibration amplitude at the resonance frequencies. The state machine platform in NI LabVIEW is used in achieving this objective. Each state is coded and a transition to the next state using interphase detection is used to run the control sequence. Each of the state action is well defined and the coupled system ensures a smart response to resonance frequencies. The knowledge of the system frequency response function and the ADVA is first studied. The performance of the ADVA is then incorporated into the design of the ADVA and implemented on an experimental setup. The result of the implementation reveals a robust adaptation of the ADVA to resonance frequencies and also reduction of vibration amplitude at all the resonance frequencies of the multi degree of freedom system.